Comparative approaches to key issues in the economic regulation of telecommunications markets in South Africa, Tanzania, Zambia, and Zimbabwe - Anthea Paelo; Genna Robb (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This paper reviews comparative approaches to key issues in economic regulation in four countries of the Southern African Development Community, and how this has been reflected in outcomes in terms of competition, prices, access, and innovation in telecommunications services. In this paper, regulatory models in South Africa, Tanzania, Zambia, and Zimbabwe are evaluated with a focus on regulation of spectrum assignment, infrastructure sharing, call termination rates, and number portability. While regulators in the four countries are generally implementing measures aimed at facilitating competition, the findings of this paper suggest that, in practice, the level of alignment between countries currently is low, and regulation could be much more effective at stimulating competition. Even finding data and information on regulatory policies and decisions in the different countries is extremely difficult, which frustrates the sharing of knowledge and evidence-based best practice. Key recommendations of the paper, therefore, relate to greater transparency by regulators and a much more serious commitment to the sharing of experiences and fostering harmonization of regulatory approaches.
Keywords: L51; L96; 330; competition; economic regulation; Southern African Development Community; telecommunications